2021
DOI: 10.24850/j-tyca-2021-01-01
|View full text |Cite
|
Sign up to set email alerts
|

Capacidad de retención de hidrocarburos del endocarpio de coco en aguas aceitosas

Abstract: En la investigación se evaluó el uso de un material filtrante, a base de endocarpio o cáscara de coco (Cocos nucifera) de forma granular, para el tratamiento de aguas contaminadas con gasoil de petróleo a nivel de laboratorio. Se construyó un sistema de filtros con tubos PVC y se empacaron con el endocarpio luego de ser triturado hasta un diámetro de 2 mm. Se utilizaron cinco cantidades de material filtrante (75, 105, 135, 150 y 165 g) y tres concentraciones de gasoil en agua (5, 10 y 15 %). Las muestras de ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…In the scientific literature, the studies on coconut residue applications, using asobtained or pre-treated residues, have focused on the following strategies: (i) application in civil construction [108][109][110][111]; (ii) use as filtering and adsorbent materials [112][113][114][115][116][117]; (iii) in ethanol production [19,26,118]; (iv) obtention of pyrolysis products [22,[119][120][121][122]; and (v) other applications [123][124][125][126].…”
Section: From Waste To Value: Byproducts From Coconut Lignocellulosic...mentioning
confidence: 99%
See 1 more Smart Citation
“…In the scientific literature, the studies on coconut residue applications, using asobtained or pre-treated residues, have focused on the following strategies: (i) application in civil construction [108][109][110][111]; (ii) use as filtering and adsorbent materials [112][113][114][115][116][117]; (iii) in ethanol production [19,26,118]; (iv) obtention of pyrolysis products [22,[119][120][121][122]; and (v) other applications [123][124][125][126].…”
Section: From Waste To Value: Byproducts From Coconut Lignocellulosic...mentioning
confidence: 99%
“…Marín-Velásquez and Cóndor-Salvatierra [115] used coconut shells as a granular filtering material to remove oil and fat from water contaminated with diesel. The water samples were contaminated with diesel oil at 5, 10, and 15% concentrations.…”
Section: Filtering Materials and Adsorbentmentioning
confidence: 99%
“…The results of studies using modified β-glucans as emulsifiers for hydrocarbon removal have indicated that modified β-glucans could increase hydrocarbon solubility by more than 11 % [ 8 ]. When coconut endocarp rich in β-glucans was used to remove hydrocarbons, such as oils and fats, from oily wastewater, the hydrocarbon removal efficiency reached up to 85 % [ 9 ]. No previous studies have investigated the use of β-glucan extracted from residual baker's yeast as an emulsifier when washing sands with high TPH concentrations.…”
Section: Introductionmentioning
confidence: 99%